Spatial and geographic factors affecting the livestock production in the Rio Platano Biosphere Reserve - Méndez S., Karina G. (Zamorano: Escuela Agrícola Panamericana, 2022, 2022)
Livestock production accounts for 30% of the world's land surface. In high to middle-income countries, livestock production has increased over the last 60 years. In Honduras, livestock represents 13% of annual GDP. Livestock production is affected by different factors, including geographic and spatial factors. This study was conducted to analyze how geographic and spatial factors affect livestock production in the Rio Platano Man and Biosphere Reserve (RPBR), Honduras. The geographical factors that affect the cadaster and intensification of the farms located in this area were analyzed. This study also used GIS-derived variables to explain, using econometric Logit and Tobit models, the cadaster and intensification of cattle farms. The results showed that the spatial factors that influence the probability that farms are cadastered or not are the distance to the core zone of the reserve and the distance to the marketplace. On the other hand, the factors that affect intensification are farm-specific factors such as area, number of cattle, forest area, and factors determined by climatic conditions such as rainfall. The study concludes that spatial and geographic factors influence some aspects of livestock production in the Rio Platano Man and Biosphere Reserve.